EFEKTIVITAS LAYANAN BIMBINGAN KELOMPOK DALAM MENINGKATKAN DISIPLIN BELAJAR SISWA SMA - Rahma Sari, Fadilla; Firman, Firman (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
Learning discipline is a mental attitude to obey rules, regulations, self-control, while adapting to external rules, even those that are restrictive and show awareness of responsibility for tasks and obligations. This study aims to determine the effectiveness of group guidance services in improving learning discipline in high school students. This study is a quantitative study with a pre-experimental research type with a one-group pretest and posttest design. The subjects in this study were 10 students of SMA N 7 Padang with certain criteria. The instrument used in this study was a questionnaire, while the data were analyzed using the Wilcoxon Signed Rank Test with the help of the SPSS 22 application. The results of the study showed a significant increase in learning discipline scores after being given group guidance services. The results of the Wilcoxon test showed a significance value of 0.005 (p <0.05), which means there was a significant difference between before and after treatment. Thus, group guidance services are proven to be effective in improving learning discipline in high school students.